Value of Biochemical Indexes of Bone Metabolism in Predicting Osteoporotic Lumbar Fractures. (23rd June 2022) - Feng, Fen; Zhou, CiLa; Huang, Ping; Zhu, QiaoLin; Wang, Gang; Zhou, Bin
Abstract : Objective . To investigate the value of bone metabolism indexes such as type I procollagen N-terminal propeptide (P1NP), 25-hydroxyvitamin D (25(OH)D), osteocalcin (OSTEOC), and parathyroid hormone (PTH) in predicting osteoporotic lumbar fractures. Methods . 120 female patients with osteoporosis treated in our hospital were selected as research objects. There were 76 cases in the fracture group and 44 cases in the nonfracture group. The relationship between the levels of P1NP, 25(OH)D, OSTEOC, and PTH and the incidence of osteoporotic lumbar fractures were detected and compared between the two groups. The predictive value of biochemical indexes of bone metabolism in patients with osteoporosis was analyzed by ROC curve. Results . The levels of P1NP and PTH in the fracture group were significantly higher than those in the nonfracture group, while 25(OH)D and OSTEOC levels were lower than those in the nonfracture group. Moreover, the levels of P1NP, 25(OH)D, OSTEOC, and PTH are important factors affecting the pathogenesis of osteoporosis. The area under the curve (AUC) of fracture in patients with osteoporosis predicted by the combination of P1NP, 25(OH)D, OSTEOC, and PTH levels was 0.886, which was greater than the AUC predicted by each index (0.796, 0.753, 0.670, and 0.824). The best sensitivity and specificity of comprehensive prediction of each index were 78.95% and 79.10%, respectively. Conclusion . The abnormal changes of P1NP, 25(OH)D, OSTEOC, and PTH in female patients with osteoporotic lumbar fracture are closely related to the occurrence of the disease. The combination of these indicators has relatively significant application value in predicting the occurrence of fracture, which is helpful to formulate and guide relevant preventive measures for female patients with osteoporotic lumbar fracture and improve the prognosis.